Toxicity assessment of Bacillus thuringiensis strains for the control of the lesser mealworm beetle Alphitobius diaperinus (Coleoptera: Tenebrionidae) = Evaluación de la toxicidad de cepas de Bacillus thuringiensis para el control del escarabajo de la cama de pollos Alphitobius diaperinus (Coleoptera: Tenebrionidae) - Perez, Melisa Paula (2025)
This study addresses the pervasive challenge of lesser mealworm Alphitobius diaperinus (Coleoptera: Tenebrionidae) infestations in poultry farming. Our aim was to select toxic Bacillus thuringiensis strains against A. diaperinus larvae and determine the fraction(s) within the bacterial cultures harboring the active metabolites responsible for this insecticidal activity. Among the 41 strains evaluated, the Argentine strain INTA Mo4-4 showed the highest toxicity. Bioassays revealed that the main virulence factors reside within the spore-crystal pellet associated with the Cry protein. These results set the basis for the development of a targeted bioinsecticide. Further research is needed to elucidate the underlying mechanisms and validate these strategies in field trials. By harnessing B. thuringiensis-based bioinsecticides, we offer a sustainable solution to mitigate A. diaperinus infestations.